Uso da proteína de semente de cânhamo para microencapsulação de nutrientes assistida por ultrassom - Cauduro, Vitoria Hagemann (2024)
In this study, for the first time a hemp seed meal extract was evaluated as encapsulant ultrasound-assisted microencapsulation. To evaluate the potential of this encapsulant material, the encapsulation of vitamin D3 or omega-3 fatty acids oily supplements was evaluated. The extract was obtained by extraction of the hydrosoluble fraction from commercial hemp seed meal, and was characterized in terms of protein and free thiol group content, as well as protein profile and elemental composition. For the microencapsulation procedures, an ultrasound probe with 3 mm tip diameter was used, operating at 20 kHz and 750 W of input power. The experimental parameters (protein concentration, ultrasound amplitude and sonication time) of the ultrasound-assisted microencapsulation were optimized by central composite rotational design (CCRD), using the microcapsule size median (D(0,5)) and nutrient conservation as response variables. The encapsulant solution and supplement volumes were kept at 1 mL and 50 µL, respectively. The produced microcapsules were characterized regarding their morphology, zeta potential, size distribution, nutrient recovery and fatty acid profile (omega-3). The optimized conditions for vitamin D3 microencapsulation were 1.53% of protein, 31% ultrasound amplitude and 53 s of sonication. For the encapsulation of the omega-3 fatty acids supplement, the optimized conditions were 1.53% of protein, 25% ultrasound amplitude and 30 s of sonication. The microcapsules obtained for both supplements showed spherical shape with no rugosity, and remained stable for up to 30 days. It was also observed that the microencapsulation was efficient in protecting the supplements from thermal degradation, since nutrient recovery and microcapsule morphology remained the same after thermal treatment. For the free supplement, losses of up to 70% of the nutrients were observed after this treatment. In this sense, the hemp seed meal extract presents great potential for application as encapsulant material using ultrasound-assisted microencapsulation. Finally, the bioaccessibility of essential (Ca, Cu, Fe, Mg, Mn and Zn) and non-essential elements (Ba, Cr and Sr) was determined for the first time in commercial hemp seed meal samples, and only Cu showed an expressive bioaccessibility (from 37 to 68%). Hence, hemp seed meal can be considered a good source of copper, without containing significant concentrations of non essential elements available for absorption by the organism.